Autistic traits in neurotypical individuals are associated with increased landmark use during navigation. Issue 1 (8th October 2018) - Blanchette, Caroll‐Ann; Amirova, Jamila; Bohbot, Veronique D.; West, Greg L.
Abstract: People adopt two distinct learning strategies during navigation. "Spatial learners" navigate by building a cognitive map using environmental landmarks, and display more grey matter in the hippocampus. Conversely, "response learners" memorize a series of rigid turns to navigate and display more grey matter in the caudate nucleus of the striatum. Evidence has linked these two structures with autism spectrum disorder (ASD) and autistic traits in non‐clinical populations. Both people with ASD and neurotypical people with higher levels of autistic traits have been shown to display more grey matter in the hippocampus and less functional activity in the caudate nucleus. We therefore tested 56 healthy participants who completed the Autism Quotient (AQ) Scale and the 4‐on‐8 Virtual Maze (4/8 VM), which determines the reliance on landmarks during navigation. We found that people who relied on landmarks during navigation also displayed significantly higher scores on the AQ Scale. Because spatial strategies are associated with increased attention to environmental landmark use and are supported by the hippocampus, our results provide a potential behavioral mechanism linking higher autistic traits (e.g., increased attention to detail and increased sensory processes) to increased hippocampal grey matter.